1999
DOI: 10.1007/s004420050953
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and oxygen isotope ratios of tree-ring cellulose for riparian trees grown long-term under hydroponically controlled environments

Abstract: Saplings of three riparian tree species (alder, birch and cottonwood) were grown for over 5 months in a hydroponics system that maintained the isotopic composition of source water in six treatments, ranging from -120 to +180‰δD and -15 to +10‰δO. The trees were grown in two greenhouses maintained at 25°C and at either 40 or 75% relative humidity, creating differences in transpiration rates and leaf water isotopic evaporative enrichment. The cellulose produced in the annual growth ring was linearly related to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 43 publications
7
119
0
1
Order By: Relevance
“…O in semiarid forest with more open canopies (Burk & Stuiver 1981;Yakir 1992;Roden & Ehleringer 1999;Barbour 2007). However, we found that the remaining trees in low-density stands (heavily thinned) with more open canopies showed consistently lower foliar d…”
mentioning
confidence: 60%
“…O in semiarid forest with more open canopies (Burk & Stuiver 1981;Yakir 1992;Roden & Ehleringer 1999;Barbour 2007). However, we found that the remaining trees in low-density stands (heavily thinned) with more open canopies showed consistently lower foliar d…”
mentioning
confidence: 60%
“…Thus biochemical reactions lead to different isotopomers of organic compounds (Augusti and Schleucher, 2007). The proportion of O and H exchanged can be considerable; for example, during cellulose synthesis, around 40 % of O and H is exchanged with the tissue water (Roden and Ehleringer, 1999;Yakir and DeNiro, 1990). The exchange with water explains to some extent the stronger relative 18 O and 2 H signal in the leaf OM compared to the stem and root OM, since the leaf water was labelled, while the stem and root water was not.…”
Section: Tracing Ommentioning
confidence: 99%
“…humidity effects on leaf evaporative enrichment, Lipp et al 1996;Roden and Ehleringer 1999b). The strong coherence of between-site d 18 O time series highlights their potential as proxy records that can be used for paleo-climate reconstruction.…”
Section: Expressed Population Signalmentioning
confidence: 99%
“…Through a series of known fractionation events, d 18 O (and d 2 H) variation derived from hydrologic inputs is incorporated into the organic matter that makes up tree rings (Yapp and Epstein 1982;White et al 1994;Roden and Ehleringer 1999b;Roden et al 2000;Treydte et al 2006;Gessler et al 2009). Tree-ring cellulose d 18 O values can be modified by variation in atmospheric humidity and the unique isotope values it possesses, by vapor pressure deficit and therefore the magnitude of leaf evaporative enrichment associated with transpiration (Edwards and Fritz 1986;Roden and Ehleringer 1999a;Wright and Leavitt 2006;Kahmen et al 2008), by variation in source water (Wright et al 1999;Roden andEhleringer 1999b, 2007) and by post-photosynthetic but pre-biosynthetic factors shown to dampen the original isotope values of sucrose made at the leaf-level before it becomes incorporated into tree-ring cellulose (Brandes et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation